The Effectiveness of Law No. 2 of 2020 concerning the Fiscal Policy Strategy of the Government of the Republic of Indonesia in Dealing with the Impact of the Covid-19 Pandemic - Sopanah, Ana; Haikal, Mohammad Fauzi Fikri (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2022)
This study aimed to analyze the effectiveness of Law No. 2 of 2020 as a fiscal policy strategy set by the government of the Republic of Indonesia in dealing with economic problems emerging driven by the Covid-19 pandemic. A total of eight people were informants of this study. Data were collected through observation, interviews, and documentation. The stages of data analysis were collecting, reducing, and presenting the data, followed by concluding. The novelty of this research is shown by the disclosure of the effectiveness of Law No. 2 of 2020 as a government fiscal policy strategy in overcoming the impact of the COVID-19 pandemic. The results showed that three functions, namely convenience, stability, and change, are dimensions of the regulatory function of the law in question, which can have a positive impact on restoring economic activities during the Covid-19 pandemic. The law, including as one of the national economic recovery programs, can be said to be effective during the pandemic.